A systematic review of the ecological, social and economic sustainability effects of community-supported agriculture - Egli, Lukas; Rüschhoff, Judith; Priess, Jörg (Frontiers in Sustainable Food Systems, 2023)
Community-supported agriculture (CSA) offers a high potential to provide synergies between ecological, economic and social sustainability aspects. While CSA is still in a niche, it has experienced rapid growth and increasing interest during the last years. An overview of sustainability impacts of CSA based on quantitative empirical work is missing, which is needed for well-informed and targeted policies and funding, as well as to tackle research gaps. Here we reviewed the literature to systematically assess empirical and quantitative findings regarding sustainability outcomes of CSA at different levels. We found that less than 30% of the 39 studies included assessed ecological sustainability aspects. If CSA farms were compared to reference systems, they mostly performed better with regard to resource use efficiency and greenhouse gas emissions. The majority of studies evaluated social aspects. While many studies showed that CSA yet fails to reach low-income households, and therefore members do not represent the average population, CSA membership improves health and sustainability behavior. Economic variables were assessed in more than half of the considered studies, but knowledge on the relative performance remains scarce. Nevertheless, first studies indicate high economic viability. Our review suggests a largely positive performance of CSA with regard to sustainability. Accordingly, if CSA would reach a bigger share in the food system, it could contribute to a transformation towards sustainable food systems. To address important knowledge gaps, we recommend the consideration of more and particularly ecological sustainability aspects, comparisons across different farming and marketing systems and the integration of knowledge from different sources such as theses and practical knowledge documented in various languages in different parts of the world.